A Comparison of Administrative Dispute Resolution Through The Administrative Court and The Ombudsman (Examining The Differences In Functions, Authority, and Effectiveness of The Two Institutions) - Allisya Destari Pratami; Hani Sri Handayani; Raihan Hadi Prama; Sultan Novaliyana Putra (Journal of Human Interaction and Social Studies, 2026)
This study examines and compares the Administrative Court and the Ombudsman as two principal institutions for resolving administrative disputes in Indonesia. The research employs a non empirical normative legal approach using statutory and conceptual methods to analyze legal norms, institutional mandates, and doctrinal principles governing both institutions. Primary legal materials consist of legislation regulating administrative courts, the Ombudsman, and public services, while secondary materials include scholarly literature on administrative law, administrative justice, and public accountability. The findings demonstrate that the Administrative Court functions as a judicial institution focused on legal adjudication and the provision of binding decisions, whereas the Ombudsman operates as a supervisory institution emphasizing maladministration review, complaint handling, and corrective recommendations. The analysis further reveals substantial differences in jurisdictional authority, legal powers, enforcement capacity, and legal consequences of institutional outcomes. The Administrative Court offers stronger legal certainty through enforceable judgments, while the Ombudsman provides greater accessibility, procedural flexibility, and responsiveness. The study concludes that both institutions perform complementary roles within Indonesia’s administrative justice system and collectively contribute to accountability, legal protection, good governance, and the improvement of public administration.